SUSTAINABLE AGRICULTURE AND COOPERATISM: WHAT POSSIBLE LINKS? - Leite, Antonio Edson [UNESP]; Batalha, Mario Otavio (Interciencia, 2016)
Cooperatives play a central role in the dynamic operation of a number of agribusiness chains. Their influence in financing, production and marketing activities of its members is widely known and has been studied. On the other hand, analyses of a possible role of Brazilian cooperatives in the dissemination of sustainable agricultural practices among its members are still scarce. Many questions have arisen in recent decades in relation to the environmental impacts caused by agricultural activities. But the matter cannot be reduced to discussions, often dogmatic and sterile, opposing agriculture to the environment. To contribute to a better understanding of this problem, this study aims to examine the role of agricultural cooperatives in the dissemination of sustainable agricultural practices among its members. The data collection method involved interviews with managers of cooperatives and producer groups, direct observation on the field, and when possible and relevant, literature reviews. It is concluded that cooperatives have promoted actions to increase producers' access to more sustainable agricultural practices, but, however, they still face difficulties in disseminating these practices among its members.